2020
DOI: 10.1002/agg2.20015
|View full text |Cite
|
Sign up to set email alerts
|

Performance of enhanced efficiency nitrogen fertilizers in green‐harvesting sugarcane

Abstract: Enhanced efficiency fertilizers (EEF) are of interest for sugarcane (Saccharum spp.) production due to the potential to reduce N losses, and improve crop yield and environmental conditions. This study was conducted to determine the effect of urea with N‐(n‐butyl) thiophosphoric triamide (NBPT) or dicyandiamide (DCD) on NH3 volatilization and sugarcane yield. The NH3 volatilization, the foliar concentration of N and S, and yield of stalk and pol were monitored in two field trials testing six N sources (urea; ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…The higher yields promoted by UI compared to U do not corroborate the findings of Barth et al. (2020) or Cantarella et al. (2018).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The higher yields promoted by UI compared to U do not corroborate the findings of Barth et al. (2020) or Cantarella et al. (2018).…”
Section: Discussioncontrasting
confidence: 71%
“…The higher yields promoted by UI compared to U do not corroborate the findings of Barth et al (2020) or Cantarella et al (2018). The first authors stated that although NBPT urea application reduced NH 3 losses by up to 60%, it promoted no sugarcane yield gains; the latter reported that NBPT added to urea reduced NH3 volatilization losses by 52%, but sugarcane yields only increased by 6%.…”
Section: Weight Of 100 Grains and Corn Yieldmentioning
confidence: 81%
See 1 more Smart Citation
“…Nitrogen is best used by the plant in soil with a pH above 5.5. N is largely responsible for this yield (Novais et al 2007;Barth et al 2020), so the N available in the soil of the area with the presence of cachaça production residues will be put to good use.…”
Section: Resultsmentioning
confidence: 99%